The Four Masterworks of the Ming Novel : Ssu ta ch'i-shu - Plaks, Andrew H., 1945- (Book collections on Project MUSE., 1987)
Andrew Plaks reinterprets the great texts of Chinese fiction known as the "Four Masterworks of the Ming Novel" (ssu ta ch'i-shu). Arguing that these are far more than collections of popular narratives, Professor Plaks shows that their fullest recensions represent a sophisticated new genre of Chinese prose fiction arising in the late Ming dynasty, especially in the sixteenth century. He then analyzes these radical transformations of prior source materials, which reflect the values and intellectual concerns of the literati of the period.Originally published in 1987.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.